What do you mean I can't write? A practical guide to business writing for agency account managers - MacMaster, Norm (Chicago: Bruce Bendinger Creative Communications, 2007)
Contents: Sixteen tips to improve your writing, now. How to write analyses. How to write formal recommendations. How to write strategies. Marketing strategies. Media strategies. Creative strategies. How to write contact reports. How to write store check reports. How to write competitive copy reports. How to write e-mails, memos, and general correspondence. How to write a speech
Keywords: Negocios